Quality Improvement of Petroleum Products Using Fuzzy Control Charts - Abdulghafour, Amjad B; Omran, Salman Hussien; Ghulam, Zina J; Rashed, Musaab K (International Journal of Natural Sciences Research, 2017)
Quality improvement is one of the most important requirements to strengthen a competitive position in our markets today. So improving the quality, will lead to decrease variations, shrinkages and so production costs hence the customers acquire the appropriate products and services to use. Control charts have an effective usage field to keep the process under control. Control charts are illustrated as graphical analysis method which defines the products whether to stay in the acceptable limits or not and as a graphical analysis technique that specifies a signal in the state of product to be out of that limits. In this paper by detecting basic concept and essentials beyond the control charts usage and the improvement; so it combined with fuzzy approach to detect the optimal limits. Hence the application of the proposed fuzzy control chart is in Al–Dura Refinery to monitor variable quality characteristics. The proposed fuzzy control chart is under vague, imprecise, uncertain, and incomplete data and based on α-level fuzzy midrange for α – cut approach. As a result of the application, it’s rational to say that constructing fuzzy control charts have a more flexible, a more convenient mathematical characterization concept and have more reasonable results than the traditional quality control chart techniques.